Sob a ótica da máscara: a introdução do luxo nos espetáculos e sua configuraçãona festa do bumba-meu-boi do Maranhão, a partir do pensamento de Jean-Jacques Rousseau - DINIZ, Jacenilde Sousa (2024)
This dissertation aims to analyze the criticism carried out by the philosopher Jean- Jacques Rousseau in the 18th century, regarding the introduction of luxury in shows, an issue highlighted by the author since his first work, Discourse on the sciences and arts. It emerges from this intention to analyze the following question: the debate on the culture of Paris and Geneva, within the scope of Parisian shows, and the Geneva fes tival, based on the thoughts of the philosopher Jean-Jacques Rousseau, presents con- figurations for thinking about the culture of Maranhão, specifically with regard to the popular festival of bumba-meu-boi, in relation to the insertion of artifices, originating from luxury? One of the aspects that make it possible to understand the idea of luxury, in the Genevan's thinking, refers to the mask of appearance, a fundamental category, for refusing the inclusion of the Parisian spectacle, in its Republic, Geneva, this is why it is essential to approach the topic. Regarding spectacles, the philosopher develops his theory in the Letter to d’Alembert on spectacles, main work in the preparation of this investigation. The analysis of Rousseau's refusal, regarding Paris fashion shows, due to the problem of luxury, inserts us, simultaneously, in the Geneva's adherence to a model of spectacle, the party, specifically, the civic festival. Therefore, given the ele- ments that enhance Jean-Jacques' resistance to French spectacles, and from the ele- ments that establish consent to the civic festival, the space opens up, for analysis, of the possible configurations in the bumba-meu-boi festival in Maranhão. As for the the- oretical contribution, this is research of a basic nature and qualitative approach, taking into account the need to understand the culture of the Geneva people, and the culture of the people of Maranhão, specifically in the party category, based on scientific pro- duction. It is worth mentioning that the categories developed are part of a Systematic Literature Review (RSL), since, in relation to the objectives, it refers to exploratory re- search, and regarding technical procedures, bibliographic and documentary research was used. Initially, the social function of the mask in ancient Greece is addressed, supported by historical and epistemological axes, in order to problematize the respec- tive function, with the role of the mask in modernity, based on Rousseau's theoretical conceptions about the mask of appearance. Furthermore, the Republic of Geneva is presented in historical terms, in detail in the 18th century, so that one can understand, from the perspective of luxury, the refusal of the Genevan philosopher, against the implementation of Parisian shows in his city's entertainment. Furthermore, the possible consequences of this intention are verified, through the hypothesis of admission of re-finement and pomp, for the bumba-meu-boi party, considering the discussion rai- sed by Rousseau in the century of enlightenment. The aim is to reflect the idea of a civic festival, in Jean-Jacques, together with the history and narratives of bumba- meu-boi. In this sense, it was necessary to point out some features of the history of bumba-meu-boi, bearing in mind that, in the parallel between past and present, the aim is to identifythe inclusion of artifices in bumba-meu-boi, that deviate from its tradi- tional proposal. The presence or absence of such artifices is noted. And, we analyze the likely results of the Geneva philosopher's thoughts, for the bumba-meu-boi festi- val in Maranhão, with the identification of the introduction of luxury. In the final con- siderations, we list some results, pertinent to the categories developed, among which, regarding the metaphor of the mask and modern theater, and how they contribute to the privatization of the scene, whether in the theater or at parties, adopting an oppo- site direction to that predicted in ancient Greece, favoring the criticism of the philoso- pher Jean-Jacques Rousseau, regarding the introduction of modern French theater in Geneva, due to its link with luxury and refinement in shows, with the idea of universality of man as a backdrop. This perspective contributes to the analysis of the bumba-meu-boi festival in Maranhão, in its relationship between past and present, with the transformations that favored the introduction of luxury, facing the reality of the cultural industry, thus making it another product in the cultural goods market.